Designing an Alumni Information System Based on UML (Unified Modeling Language) - Sitorus, Zulham; Pranoto, Sugeng; Sutiono, Sulis; Arief, Muhammad (Cattleya Darmaya Fortuna, 2023)
This research designed a UML-based Alumni Information System for SD IT Jabal Nur Tebing Tinggi. The stages involve collecting data through observation and interviews, followed by designing UML using use case, activity, sequence, and class diagrams. The aim is to facilitate collaboration between schools and system developers, providing a visual depiction of admin and system interactions in managing alumni data. Although still at the design stage, the results provide a strong basis for further implementation, with the potential to increase efficiency and support future school development. The suggestion involves a system implementation phase to test the effectiveness of the design, accompanied by clear documentation for system maintenance and new user training.